L’observation des comportements sécuritaires par les pairs dans une usine d’assemblage : le cas Paccar - Patrick Garand; Mario Roy; Lise Desmarais (Perspectives Interdisciplinaires sur le Travail et la Santé)
In occupational health and safety literature, supporters of the systemic approach and those of the behavioral approach are often presented as belonging to two opposing camps. Each group, with research to back it up, attempts to demonstrate its ability to prevent and reduce accident rates within organizations. This article presents the difficulties and effects of using a peer-based behavior observation process in a manufacturing setting that already had a well-structured OHS program. This case study is based on field observations, a review of available documents (policies, meeting reports, and detailed statistics, etc.) and twenty semi-structured interviews with individuals involved in OHS activities. The results suggest that the two approaches were not incompatible but that their relationship was not problem-free. We noticed in particular that a lack of clarity in role definitions sometimes led to conflicts between the groups in charge of their management. Moreover, behavior observation by peers had some definite advantages according to the respondents. It was perceived as a useful tool for making workers more aware of, involved in and responsible for OHS, which would make it an interesting complement to the systemic approach. To this end, we noted a positive correlation between the frequency of observation sessions and the number of incidents reported by workers. The corrections made after the reports subsequently reduced system-related risks. Consequently, a program initially designed to modify behavior had effects that went beyond the original intention. The behavior observation process was a delicate one. There were difficulties related to freeing up and training observers, to organizing the committee in charge of the process, and to establishing harmonious relations with the organization’s OHS committee.